Uji Infeksi Cylindrocladium sp Pada Tiga Klon Hibrid Turunan Eucalyptus grandis x Eucalyptus urophylla di PT. Toba Pulp Lestari, Tbk Porsea - R.R. Malau; R. Rambey; E.B.M Siregar (Peronema Forestry Science Journal, 2016)
One disease that attacks the seeds of eucalypts is Cylindrocladium. Cylindrocladium foliar disease-causing spot and foliar blight. PT Toba Pulp Lestari developed many types of clones by vegetative means. This research aimed to characterize the symptoms of the disease leaves, measuring the level of intensity of the attacks, spacious attacks and reactions of plants (resistance) against infection Cylindrocladium sp on three clones of Eucalyptus hybrid. Clones test in the IND 68, IND 70, IND 73. Inoculation was done by spraying. Each plant was sprayed as many as 10 ml of inoculant to the entire leaf surface evenly with spore density of 3.44 x spores/cc. Observation of symptoms is done every day since the inoculation held. The results showed the same symptoms. Symptoms begin with yellowish spots and will widen (necrotic) and continues in death of leaf tissue. The intensity of the attacks on three clones tested showed no real effect from the third until the sixth observation after the inoculation. The test results also showed that all the clones are infected 100%. Key words : Eucalyptus sp, Cylindrocladium sp, Infection Test, Resistant